Menegakkan Keadilan Hukum dalam Menghadapi Tantangan dan Upaya di Indonesia - Afdal Surya Hamid; Sasmi Nelwati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Abstract This article aims to analyze the concept, urgency, as well as the dynamics and challenges of upholding the rule of law with justice in Indonesia. The research method used is a literature study by reviewing various reliable sources such as books, journals, and laws and regulations. The results show that the upholding of the rule of law with justice in Indonesia still faces various problems, such as the behavior of state apparatus that has not been good, the potential for social conflict and violence, as well as the weakness of law enforcement itself. Efforts that can be made are to strengthen the integrity of law enforcement officials, increase public legal awareness, and carry out comprehensive legal system reforms. Thus, the upholding of the rule of law with justice can be realized and provide legal certainty and protection of the rights of the community.